VD_FINDINFO HC / 2013 / 669 vom 14. November 2013 - VD Tribunal cantonal (2013)
AVANCE DE FRAIS, ARBITRAIRE DANS L'APPLICATION DU DROIT, RÉDUCTIONEN GÉNÉRAL | 16 al. 7 LPers-VD, 16 LPers-VD, 98 CPC (CH), 104 CDPJ, 10 TFJC (2010), 18 al. 1 TFJC (2010)